(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
The paper presents a method for determining the electromagnetic parameters of the linear dynamic model of the induction motor with a three-phase stator winding in a star connection (with the star neutral point isolated) and a polyphase rotor winding (simple cage type) in the short circuit - based on the transient response test in the stator phase electric current intensity, upon the sudden connection of a direct voltage source in the electrical circuit of the stator phase windings A and B, corresponding to the particular topology of the three-phase stator electrical circuit, in which the stator phase windings B and C have galvanically connected input terminals. DOI: https://doi.org/10.36801/apme.2024.1.1